2022
DOI: 10.1007/s10198-022-01453-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital resource utilisation from HPV-related diseases in England: a real-world cost analysis

Abstract: Background and objective HPV (human papillomavirus) is the virus most often responsible for sexually transmitted infections. The burden of HPV-related diseases on hospital resources represents a major public health problem. The objective of this study was to quantify the lifetime economic burden of HPV-related diseases based on hospital resources from the perspective of National Health Service (NHS) in England. Methods Patients’ data were extracted, anonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 21 In contrast, a recent study in England revealed that hospitalization costs are greater for women than for men. 22 As of 2017 in Spain, the estimated annual cost of anal cancer attributed to infection from any type of HPV genotype was 4.42 million €, and the annual cost of penile cancer attributed to any type of HPV increased to 1.58 million euros. 23 Compared with the costs of hospitalization for other cancers, anal cancer in men and women and penile cancer in men represent a slightly lower cost than the estimated cost of cervical cancer in hospitalized women, 4,446€.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In contrast, a recent study in England revealed that hospitalization costs are greater for women than for men. 22 As of 2017 in Spain, the estimated annual cost of anal cancer attributed to infection from any type of HPV genotype was 4.42 million €, and the annual cost of penile cancer attributed to any type of HPV increased to 1.58 million euros. 23 Compared with the costs of hospitalization for other cancers, anal cancer in men and women and penile cancer in men represent a slightly lower cost than the estimated cost of cervical cancer in hospitalized women, 4,446€.…”
Section: Discussionmentioning
confidence: 99%
“…Our study data showed that patients with CA have a large financial burden of medical care, with the mean cost associated with diagnostics and treatment for CA per visit in Guangdong and Jiangsu being $509.55 and $625.27 respectively. A real-world cost analysis of England showed that lifetime costs per patient diagnosed with anogenital warts was equal to £872 (£884 and £856 for men and women, respectively) [ 27 ]. In Peru, given a population of 18.4 million adults between 18 and 60 years of age and a CA prevalence of 2.28%, the annual cost of treating CA was 25.1 million USD (uncertainty interval 16.9, 36.6) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genital warts are the most prevalent HPV-associated disease in men and are of substantial cost to the healthcare systems [ 90 , 91 ]. Oropharyngeal and anogenital cancers in men are often diagnosed late because there are no routine screening methods, and management is still being researched [ 92 , 93 , 94 ].…”
Section: The Case For Vaccinating Boys and Menmentioning
confidence: 99%